Daya Tampung Beban Pencemaran Sungai Batang Lembang Segmen Kota - Aulia Azhar (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2017)
This study aimed to determine the pollution load capacity of Batang Lembang River segment of Solok City from upstream to downstream to TSS, BOD and COD parameters. This research is descriptive quantitative by using Qual2KW method with the location point of sampling at representative of use of land along the river of atang lembang as much as 15 point location of sampling from upstream to downstream. The results showed that for the Total Suspended Solid Parameters (TSS) seen from upstream to downstream at 1, 2, 4, 5, 6, 7, 9, 10, 13, 15, the reduced pollution load should be 5,832.00 Kg / day ( (Segment 5), 5,378.40 Kg / day (segment 6), 4,082.40 Kg / day (segment 7), 23,490.00 Kg / day (segment 9), 5,248.80 Kg / day (segment 10), 12,979.44 Kg / day (segment 13) and 6,486.48 Kg / day (segment 15); For BOD Parameters on the 1st, 3rd, 9th, 10th, 11th, 12th and 13th Sections, the toll road shall be reduced by the pollution load of 453.60 Kg / day (segment 1), 336.96 Kg / day (segment 3), 324.00 Kg / day ( (Section 10), 129.60 Kg / day (segment 11), 194.40 Kg / day (segment 12), 207.36 Kg / day (segment 13) and 77.76 Kg / day (segment 15); For COD Parameters For COD Parameters in 3, 5, 8, 10, 12, 13 and S segments 15 shall be reduced by the pollution load of 16.264.80 Kg / day (segment 3), 3,888.00 Kg / day (segment 5), 4,879.44 Kg / day ( Segment 8), 12,214.80 Kg / day (segment 10), 13,504.32 Kg / day (segment 12), 4,451.76 Kg / day (segment 13) and 3,039.12 Kg / day (segment 15); The pollution loads of TSS, BOD and COD parameters need to consider the environmental aspects, covering the location / area, demography, pollutant source and water quality